2019
DOI: 10.1097/gox.0000000000002216
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fat Grafting in Alleviating Neuropathic Pain: A Critical Review of the Literature

Abstract: Background: Neuropathic pain is one of the more severe types of chronic pain and presents a great challenge as response to medical therapy remains often unpredictable. With the opioid epidemic and the search for ways to avoid narcotics, physicians are seeking other modalities to treat neuropathic pain. In recent years, surgeons have explored various surgical avenues to improve outcomes. The aim of this review was to evaluate the current clinical evidence regarding the efficacy of fat grafting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…However, fat grafting has also been advocated as adjuvant treatment in implant-based reconstruction in order to optimize the implant's interaction with the surrounding tissue and improve acquired breast contour deformities [38]. Moreover, fat grafting has been proven effective in revitalizing the microvascular damage and interstitial fibrosis found in chronically radio-damaged tissues [17,20,39,40]; thus, it can be exploited in breast reconstruction for both its regenerative and volumetric properties, allowing for use in lower-volume implants, which remain a foreign body, reducing postmastectomy pain and improving breast contour and consistency, leading to a more natural-looking breast [10,14,16,19,20,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fat grafting has also been advocated as adjuvant treatment in implant-based reconstruction in order to optimize the implant's interaction with the surrounding tissue and improve acquired breast contour deformities [38]. Moreover, fat grafting has been proven effective in revitalizing the microvascular damage and interstitial fibrosis found in chronically radio-damaged tissues [17,20,39,40]; thus, it can be exploited in breast reconstruction for both its regenerative and volumetric properties, allowing for use in lower-volume implants, which remain a foreign body, reducing postmastectomy pain and improving breast contour and consistency, leading to a more natural-looking breast [10,14,16,19,20,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous fat transplant (AFT) has been associated with increased skin trophism and vascularization, reduced post-operative pain, and improved cosmetic results [9][10][11]. However, the debate is still ongoing over fat grafting in breast reconstruction due to some important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cell therapy modalities included in the present study promoted MSCs migration and proliferation [ 51 , 52 , 54 57 ]. In addition to their cellular differentiation potential, the paracrine activity of MSCs interact with the microenvironment, enhancing tissue regeneration and modulating inflammation, promoting T and B cell proliferation, and NK cell activity [ 25 , 26 , 73 ]. The power of regenerative medicine relies in the signalling and mutual interaction patterns between stem cells and environment [ 74 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term clinical benefit-reduction of need for orthodontic intervention, 16,19,20 improving anteroposterior development of the maxilla, 17 and increasing cleft surgery-first orthognathic surgery 54 -of attenuating posterior transverse maxillary collapse by covering lateral relaxing incisions with buccal fat flaps should also be explored in future investigation when the cohort of included patients reach skeletal maturity. Although a growing body of literature has shown that autogenous fat tissue could promote wound healing, improve scar quality, and reduce postoperative pain, [55][56][57] other potential advantages of using buccal fat flap in palatoplasty such as time to recovery of feeding postoperatively and quality of tissue at lateral palatal recipient regions should be addressed by a well-delineated research study design.…”
Section: Ementioning
confidence: 99%